Evaluation of the Implementation of Digital Literacy Programs in Improving School Quality at SD Negeri Rempoa 01 South Tangerang City - Sari*, Ika Puspita; Syarif, Moh. Suryadi; Muljono, Hery (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The purpose of this research is to evaluate the Implementation of the Digital Literacy Program to Improve School Quality at SD Negeri Rempoa 01. This research used a CIPP evaluation model which includes four aspects: (1) context, (2) input, (3) process, and (4) product. The data were collected through interviews, observation, and documentation. The interview was conducted with the School Principal, Homeroom Teacher, and ICT Teacher. The data were analyzed qualitatively using the Interactive Analysis Model by Miles and Huberman which consists of gathering data, reducing data, displaying data, and drawing conclusions. The results of the study show that: (1) Aspects of context evaluation, the digital literacy program at SD Negeri Rempoa 01 Kota Tangerang Selatan is not by the vision, mission, goals, and objectives of the existing programs at the school. The results of the SWOT analysis, an internal lack of strength and an external lack of opportunities. 2) In the input evaluation aspect, school-owned supporting resources exist but are not by the provisions. This can be seen from the incomplete curriculum, teaching materials, and media. (3) In The process evaluation aspect, teachers have appropriate academic qualifications but they are not optimal in guiding the process of implementing their learning to help the students be more critical, creative, and innovative in making learning work. (4) ) Aspects of product evaluation include students' attitudes, knowledge, and skills, namely being more responsible for digital literacy activities, but in terms of knowledge competency still needs to be improved. The results of student academic achievement based on the value of the Minimum Competency Assessment (AKM) which is part of the National Assessment (AN) in exchange for the National Examination (UN) show that the acquisition of advanced literacy proficiency scores is 3.45%, proficient is 86.21%, basic is 6.9%. The results concluded that 89.66% of students had a proficient or proficient level of competence.